Giuseppe Dessì tra traduzioni e edizioni Una raccolta di saggi - Anna Dolfi (Moderna/Comparata, 2013)
With the 100th anniversary of Giuseppe Dessí's birth approaching, in 2009, the Committee in charge of the celebrations launched in a widespread dissemination activity of the writer's work in many European countries. And since the translations (the main objective of the project) required a complex knowledge of the author, his style, the dialogue and the difference with the reference culture, it was suggested to study and promote them not only through the reconstruction of the history and typicality of the author's narrative path, but also through the reconstruction of his scarce reception abroad within the framework, in the case of Dessí, of the presence, outside national borders, of Italian literature in the second half of the 20th century. Through the examination of books, editorial catalogues, magazines, anthologies, and thanks to the commitment of scholars and young collaborators of Italian and foreign universities, it is now France, England, Spain, Germany, the Netherlands, Poland, Hungary, Ukraine, Finland, Sweden and many more at the centre of the attention, with their reading preferences and aversions, together with Italy, and with the themes, stories, characters of the writer to whom this book is dedicated.